PEDAGOGICAL ASPECTS OF FORMING INFORMATION FLOW ANALYSIS SKILLS IN UNIVERSITY STUDENTS (Scientific journal of the Fergana State University, 2024)
In this article, the formation of information culture in them is a very urgent problem in protecting young people, who are the future of the intelligentsia, from the information storm created in the world community, and the pedagogical aspects of forming the skills of analyzing the flow of information in students are highlighted. Also, an important task of media pedagogy, which is a new direction in pedagogy, is the issue of the unification of the information space of states and peoples, the formation of the culture of working with information among young people, especially students, in their perception of reality (status of information) in political, social and other aspects.